Characteristics of the gravity field of predictive oil-gas areas in the DDD region according to satellite model EGM08 and gravity measurements at the beginning of the XX century - V. G. Bulatsen; L. Ya. Khalyavina; T. E. Borisyuk (Геофизический журнал, 2019)
Gravimetric information is the basis for mineral exploration. The foundations of resource research in Ukraine were started by a large-scale gravimetric survey performed by the Poltava Gravimetric Observatory (PGO) in 1926—1934. Modern geological exploration uses information from Earth remote sensing, obtained with the help of special equipment installed on space vehicles. Satellite data on the distribution of gravitational anomalies (Dg) are displayed in the model of the gravitational field of the Earth EGM08, created for the practical use on the data of the special missions CHAMP and GRACE. The features of the structure of the gravitational field for perspective oil and gas areas located in the Dnieper-Donetsk depression (DDD) are considered, based on the model EGM08 and gravity measurements performed in the first half of the XX century. This al-lows: 1) to test the geological information of the model EGM08; 2) to assess the nature of the age-old changes in gravity in areas that have a specific and similar geological structure by comparing these data sets. For most sites it is typical: 1) the complex structure of the field of gravity, the presence of local “potential wells” with fluctuations in gravity anomalies of 10―30 mGl, characteristic of fault zones; 2) mainly negative values of anomalies by area (Dg < 0), which is typical for the rocks with reduced density and increased porosity. These results confirm the correct nature of the model EGM08. The secular changes of the gravity dDg for the corresponding points were estimated as the anomaly difference according to the EGM08 model data and the classical measurements previously reduced to the WGS84 system. For most points, there are: 1) a multidirectional change in dDg; 2) for about 20 % of points the values |dDg| ³ 5 mGl, which does not exclude the influence of local technogenic or geophysical factors. A statistically significant increase in the age-old change in gravity on + 3.3 mGl was found for the northwestern section of site No. 2 (Lokhvitsa segment of DDD), where the density of groundbased measurement points is high.